The Polemics of C.L.R. James and Contemporary Black Activism - D. Clennon, Ornette (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book draws on case examples of contemporary black activism in South Manchester and contrasts them with events that surrounded C.L.R. James and his activism between 1935 and 1950. In doing so, the author considers what Brexit, the Labour Party and Theresa May's audit on racism in the UK have in common with the wartime decline of the British Empire, the rise and fall of the trade unions and the Italian invasion of Ethiopia. Clennon dialogues with James' theoretical frameworks around capitalism, neoliberalism and post-colonialism, and uses this creative interplay of ideas to help make sense of contemporary events and issues of social justice from a UK ethnic minority perspective. Using Fanon, Gordon, Marx and Chakrabarty amongst others, the study explores James' take on dialectical materialism and uses this as an ongoing analytical tool throughout the volume with which he weaves an uneasy path between post-colonial and post-Marxist theories. The Polemics of C.L.R. James and Contemporary Black Activism will be of interest to students and scholars across a range of social science disciplines, including sociology, cultural studies, education and black studies. .
Keywords: Social sciences.; Social structure.; Social inequality.; Social sciences -- Philosophy.; Ethnicity.; Sociology, Urban.; Social service.; elektronické knihy; electronic books